STRATEGIES FOR IMPROVING FINANCIAL LITERACY IN RURAL COMMUNITIES: A LITERATURE REVIEW - Silvia Ekasari; Kholid Ansori; Nurussama (Adiba Aisha Amira, 2023)
This study aims to identify and analyze effective strategies that can be applied to improve financial literacy in rural communities. The research method used was a literature review. The results show that improving financial literacy in rural communities can be achieved through a multidimensional approach that includes developing locally appropriate educational materials, improving access to financial technology, targeted technology education, and cooperation between the government, private sector, and local communities. Key factors influencing success include adaptation of teaching methods to socio-cultural conditions, implementation of inclusive financial technologies, and trust building between financial service providers and rural communities.